Load balancing algorithms for Jacksonian networks with acknowledgement delays - Bovopoulos, A.D.; Lazar, A.A. (Conference on Computer Communications, 1989)
Load-balancing algorithms for Jacksonian networks are derived. The state of the network is represented by the total number of packets for which the source has not yet received an acknowledgement. The networks studied are subject to state-independent routing and state-dependent and state-independent flow control. The objective is to maximize the throughput of the network so that the end-to-end expected packet time delay does not exceed an upper bound. The optimal flow control is shown to be of a window type, while the routing policy balances the traffic inside the network. Several load-balancing algorithms are evaluated.< >